Alexithymia is associated with insomnia in Chinese patients with schizophrenia - Cai, Fangfang; Jiang, Huixia; Tong, Siyu; Zhou, Siyao; Wang, Mengpu; Sun, Shiyu; Liu, Jie; Xu, Yao; Lin, Nankai; Dai, Jiajing; Wang, Xinyao; Wang, Wei; et al. (Frontiers in Psychiatry, 2023)
Background: Sleep disorders are prevalent among patients with schizophrenia and are associated with several negative consequences.Although, researchers have recently suggested that sleep disorders have a close correlation with alexithymia, and schizophrenia also has a strong correlation with alexithymia, there have been few studies on the relationships between schizophrenia, sleep disorders and alexithymia.Therefore, this study aimed to explore the relationships between psychiatric symptoms, alexithymia and sleep problems in patients with schizophrenia so as to provide a reference for the clinical treatment of this comorbidity.In total, 977 patients with schizophrenia were recruited for this study. The Insomnia Severity Index (ISI) was used to assess sleep disorders, and the Positive and Negative Syndrome Scale (PANSS), Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and Toronto Alexithymia Scale (TAS) were used to evaluate clinical symptoms, cognitive functions and the ability to express emotion, respectively.The results indicated that the PANSS subscales (G-subscore) and TAS group were risk factors for insomnia in schizophrenia patients (all p < 0.05). The mediation model showed the standardized path coefficients from schizophrenia to alexithymia (β = 0.104, p < 0.001) and from alexithymia to insomnia (β = 0.038, p < 0.001) were statistically significant.The results of this study indicated that alexithymia is associated with sleep disturbance in patients with schizophrenia. These findings may provide a new avenue for the treatment of schizophrenia patients with sleep disorders.